CLARIN in the Low Countries. (Ubiquity Press, 2017)
"This book describes the results of activities undertaken to construct the CLARIN research infrastructure in the Low Countries, i.e., in the Netherlands and in Flanders (the Dutch-speaking part of Belgium). CLARIN is a European research infrastructure for humanities and social science researchers that work with natural language data. This book introduces the CLARIN infrastructure, describes various aspects of the technical implementation of the infrastructure, and introduces data, applications and software services created in the Low Countries for a wide variety of humanities disciplines. These enable researchers to accelerate their research activities and to base their conclusions on a much larger and richer empirical base than was possible before, thus providing a basis for carrying out groundbreaking research in which old questions can be investigated in new ways and new questions can be raised and investigated for the first time. Given CLARIN's focus on language data, linguistics and particularly syntax are prominently present. However, other humanities disciplines that work with natural language data such as history, literary studies, religion studies, media studies, political studies, and philosophy are represented as well. The book is a must read for humanities scholars and students who want to understand and use the potential that the Digital Humanities offer, as well as for computer scientists and developers of research infrastructures, in particular for researchers working on the CLARIN infrastructure in other countries."